Changes of starch composition by postflowering environmental conditions in kernels of maize hybrids with different endosperm hardness - Martínez, R. D. (2017)
Fil: Martínez, R. D. Universidad Nacional de Mar del Plata. Facultad de Ciencias Agrarias; Argentina.